Authoritarian Parenting Style of the Main Character in the Novel a Child Called “It” by Dave Pelzer - Safitri, Nada Fira; Pertala, Erik Candra; Hestiana, Siska (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
The research entitled